Analisis Implementasi Strategi Email Marketing Dalam Meningkatkan Loyalitas Pelanggan Perusahaan B - Chiquitita, Tesalonika Christina Chiquitita; Wolor, Christian Wiradendi; Utari, Eka Dewi (Universitas Sains dan Teknologi Komputer, 2025)
This research is designed to investigate how the use of email marketing techniques can enhance customer loyalty at Company B. In the current digital landscape, email marketing is seen as a powerful tool for fostering connections with customers while promoting sustained engagement over time. By utilizing this approach, businesses can deliver valuable information, promotions, and content to customers in a more tailored and relevant fashion. To achieve these goals, this research adopts a descriptive analytic approach with a qualitative focus, where information is gathered through on-site observations, comprehensive interviews, and distributing surveys to staff directly engaged in the email marketing efforts at Company B. The results of the study indicate that the execution of email marketing strategies is being performed effectively and strategically, with the backing of sufficient internal resources, such as a digital marketing team and a campaign automation system. Many participants believe that personalizing content, effective communication, and the regularity of email dispatches are functioning well. Furthermore, most employees indicated that this strategy has played a pivotal role in bolstering customer loyalty and aiding in the development of stronger connections between the company and its customers. Therefore, it can be concluded that the application of email marketing strategies within Company B has a beneficial effect on enhancing customer relationships and should be regarded as a primary tactic for maintaining customer loyalty over the long term.